Pengaruh Pendampingan Belajar Orang Tua Terhadap Hasil Belajar PAK-BP Pada Siswa Kelas VII SMP Katolik Gonzaga Tomohon - Hadi Ignatius Untu; Asri Rumagit (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
Parents as educators first and foremost, in fact, do not carry out their responsibilities in accompanying children to learn at home. Lack of learning assistance has a negative influence on children so that their learning outcomes are less satisfactory. Such problems were also found in grade VII students of Gonzaga Tomohon Catholic Junior High School which prompted researchers to raise a study entitled